LITERASI MUAMALAH PADA JAMAAH MASJID JAMI’ AL-MUNAWWAROH KELURAHAN KARYAMULYA KECAMATAN KESAMBI KOTA CIREBON DALAM RANGKA MEMAJUKAN EKONOMI SYARIAH - Jefik Zulfikar Hafizd; Ahmad Khoirudin (Universitas Galuh, 2023)
Fiqh Muamalah examines the relationship between humans in the economic field. An understanding of muamalah that is in accordance with Islamic teachings or the application of Islamic Economics is important for Muslims so the socialization of muamalah is very important to the community. The focus of service is da'wah about sharia economics to the congregation of Al-Munawwarah Mosque. Public awareness or understanding of sharia economics is very important because it is the obligation of Muslims to carry out all sharia, including in muamalah affairs. This service aims to preach Islamic Economics which has benefits, including 1) Mosque congregations can understand well about Islamic economics through the delivery of muamalah literacy. With a good understanding, pilgrims can practice economic activities that are in line with Islamic values or sharia principles and avoid prohibitions in economic activities such as usury, gharar, and maysir; and 2) Sharia economic progress can be achieved if all Muslims can understand and carry out economic activities in accordance with sharia principles.